2016
DOI: 10.1073/pnas.1604780113
|View full text |Cite
|
Sign up to set email alerts
|

Stabilin-1 expression defines a subset of macrophages that mediate tissue homeostasis and prevent fibrosis in chronic liver injury

Abstract: Macrophages are key regulators of fibrosis development and resolution. Elucidating the mechanisms by which they mediate this process is crucial for establishing their therapeutic potential. Here, we use experimental models of liver fibrosis to show that deficiency of the scavenger receptor, stabilin-1, exacerbates fibrosis and delays resolution during the recovery phase. We detected a subset of stabilin-1 + macrophages that were induced at sites of cellular injury close to the hepatic scar in mouse models of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(126 citation statements)
references
References 29 publications
8
113
0
5
Order By: Relevance
“…Importantly, hepatic inflammation can be substantially improved by treatment with a specific MDA antibody, indicating that MDA epitopes contribute to the inflammatory phenotype in the liver of WD‐fed Ldlr –/– mice. Of note, deficiency of CD36 and MSR1, which we found to be involved in MDA‐induced inflammation, also results in reduced hepatic inflammation in this model, and other receptors that have been implicated in the recognition of MDA epitopes may also contribute to it . We show decreased expression of CXCL1 and CXCL10 in the livers of LR04‐treated mice, which is consistent with the important roles of these chemokines and their receptors in other models of hepatic inflammation and their potential as biomarkers for fatty liver disease in humans .…”
Section: Discussionsupporting
confidence: 85%
“…Importantly, hepatic inflammation can be substantially improved by treatment with a specific MDA antibody, indicating that MDA epitopes contribute to the inflammatory phenotype in the liver of WD‐fed Ldlr –/– mice. Of note, deficiency of CD36 and MSR1, which we found to be involved in MDA‐induced inflammation, also results in reduced hepatic inflammation in this model, and other receptors that have been implicated in the recognition of MDA epitopes may also contribute to it . We show decreased expression of CXCL1 and CXCL10 in the livers of LR04‐treated mice, which is consistent with the important roles of these chemokines and their receptors in other models of hepatic inflammation and their potential as biomarkers for fatty liver disease in humans .…”
Section: Discussionsupporting
confidence: 85%
“…MDA gives rise to more complex lipid motifs, such as a highly reactive and immunogenic 4-methyl-1,4-dihydropyridine-3,5-dicarbaldehyde, also termed malondialdehyde-acetaldehyde (MAA). As oxidation-produced DAMPs, MDA epitopes are recognized by multiple arcs of innate immunity, including the scavenger receptor SR-A1, the Fcγ receptor CD16, complement factors H and C3a, stabilin-1, and a number of natural antibodies [7377]. Immunization of mice with MAA-modified LDL was atheroprotective [78].…”
Section: Inflammatory Effects Of Lipid Oxidation End Productsmentioning
confidence: 99%
“…The impact of Ly6C lo monocytes in isolation on the induction and resolution of fibrosis has been evaluated with conflicting results. In models of chronic CCl 4 ‐induced liver fibrosis, Ly6C lo monocyte‐derived macrophages were found to be critical for tissue repair, with persisting fibrosis associated with decreased levels of Ly6C lo monocyte‐derived macrophages 37 , 94 . In contrast, a recent study from MacDonald and colleagues 40 using a thioacetamide‐induced chronic fibrosis model showed that blockade of macrophage colony‐stimulating factor receptor (CSF1R, also known as CD115), the receptor for CSF‐1, resulted in decreased Ly6C lo monocyte‐derived macrophages in parallel with decreased fibrosis, suggesting that Ly6C lo monocyte‐derived macrophages are critical for driving fibrosis.…”
Section: Monocytes As Drivers Of Fibrosis or Resolution Of Fibrosis?mentioning
confidence: 99%